Synthesis and characterization of new 8-aryl-1,3-dimethylxanthine derivatives/ Yeni 8-aril-1,3-dimetilksantin türevlerinin sentezi ve karakterizasyonu - Abdullah Najeeb, Hamsa
Xanthine is a heterocyclic aromatic organic compound belongs to purine bases. It has many derivatives present in nature, such as caffeine in coffee leaves and beans, theophylline in black and green tea leaves, and theobromine in seeds of the Theobroma cocoa tree. Because of the similarity between the xanthine skeleton and the skeleton of two important purine derivatives, adenine and guanine, it is considered as an important therapeutic molecule. Thus, recently the treatments of various diseases are targeted by xanthine derivatives. The diversity of the substituted groups in xanthine molecules gives it importance to be a drug candidate in many treatments, including anti-parkinsonism and anti-Alzheimer's, anti-cancer, anti-asthmatic and bronchodilation, anti-diabetic, anti-depressant, anti-inflammatory, diuretic, anti-microbial, sirtuin inhibitors and ligands of adenosine receptor subtypes. C-8 position in the xanthine molecule have a significant impact on biological activity. So many prodrugs were designed through 8-substitution. In this thesis, new 8-substituted xanthine derivatives were synthesized by reacting the corresponding aldehydes with 5,6-diamino-1,3-dimethyluracil to form Schiff bases and then performing the ring-closing reaction using iodine. Spectroscopic methods were applied to confirm the structures of the synthesized xanthine derivatives. The poor solubility of these derivatives in water and common organic solvents limited the techniques used to characterize the products, especially the 13CNMR analysis. Experimental attempts have been made to solve this solubility problem. Thus, the xanthine derivatives were reacted with sodium hydroxide to form xanthine sodium salts. The solubility of the products in water significantly improved and the product completely dissolved in water, but the expected results could not be obtained from NMR analysis which was performed in D2O. Then we planned to improve the solubility of the products in common organic solvents by converting it to silyl derivatives. The silyl derived Schiff bases were obtained by reacting silylated salicylaldehyde derivative and 5,6-diamino-1,3-dimethyluracil. In the final step, silyl derived xanthine derivative, which was completely soluble in dichloromethane, was obtained.